2021
DOI: 10.1371/journal.pone.0256442
|View full text |Cite
|
Sign up to set email alerts
|

The blood transcriptome prior to ovarian cancer diagnosis: A case-control study in the NOWAC postgenome cohort

Abstract: Epithelial ovarian cancer (EOC) has a 5-year relative survival of 50%, partly because markers of early-stage disease are not available in current clinical diagnostics. The aim of the present study was to investigate whether EOC is associated with transcriptional profiles in blood collected up to 7 years before diagnosis. For this, we used RNA-stabilized whole blood, which contains circulating immune cells, from a sample of EOC cases from the population-based Norwegian Women and Cancer (NOWAC) postgenome cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
2
0
0
Order By: Relevance
“…The estimated proportions of WBCs in our study deviated from the expected range, but this deviation also has been observed in other recent studies based on the NOWAC postgenome cohort [41, 42]. This indicated a bias that could be explained by the deconvolution technique or data preprocessing [41, 43]. Still, absolute differences in estimated WBCs across BMI categories were modest, and the top‐ranked genes identified in our models were very similar, indicating that these genes were not substantially influenced by distributions of WBCs.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The estimated proportions of WBCs in our study deviated from the expected range, but this deviation also has been observed in other recent studies based on the NOWAC postgenome cohort [41, 42]. This indicated a bias that could be explained by the deconvolution technique or data preprocessing [41, 43]. Still, absolute differences in estimated WBCs across BMI categories were modest, and the top‐ranked genes identified in our models were very similar, indicating that these genes were not substantially influenced by distributions of WBCs.…”
Section: Discussionsupporting
confidence: 76%
“…As skewed WBC proportions due to differences in BMI could have influenced our BMI analyses, we included these estimated cell proportions in our fully adjusted models [40]. The estimated proportions of WBCs in our study deviated from the expected range, but this deviation also has been observed in other recent studies based on the NOWAC postgenome cohort [41,42]. This indicated a bias that could be explained by the deconvolution technique or data preprocessing [41,43].…”
Section: Discussionsupporting
confidence: 66%